Experimental food allergy to peanut enhances the immune response to house dust mite in the airways of mice. Issue 1 (20th September 2016) - Utsch, L.; Logiantara, A.; van Ree, R.; van Rijt, L. S.
Summary: Background: Food allergy has been associated with an increased risk for the development of allergic asthma. Asthma is a risk factor for the development of an anaphylactic response to food allergens. An immunological interplay between sensitization to different allergens in different compartments of the body might be involved. Objective: To evaluate the immunological interplay between intragastrical peanut (PE) sensitization and respiratory sensitization to house dust mite (HDM) allergens. Methods: BALB/c mice were intragastrically sensitized to peanut or sham‐sensitized and challenged systemically to PE. Between sensitization and challenge, mice were intranasally exposed to HDM extract or PBS, as a control. The response to HDM (eosinophil recruitment, cytokine response, HDM‐specific immunoglobulins and airway hyper‐reactivity) and to PE (cytokine response, mast cells in gut, mMCP‐1 in serum and body temperature) was assessed. Results: A preceding PE sensitization increased HDM‐induced production of IL‐4, IL‐5, IL‐13 and IFNγ in lung‐draining lymph nodes and total IgE levels in HDM‐sensitized mice. However, recruitment of inflammatory cells to the airways or airway hyper‐reactivity was not aggravated in PE/HDM double‐sensitized mice. Alternatively, HDM‐induced airway inflammation did not significantly affect the immune response or the anaphylactic response to a systemic challenge with peanut. Conclusion and Clinical Relevance: Our data show that a preceding peanut sensitization boosted IgE‐ and HDM‐specific Th2 response in the airways in mice. It contributes to the understanding of the underlying immunological mechanism of polysensitization which often occurs in allergic individuals over time.